TINJAUAN KETIDAKLENGKAPAN RESUME RAWAT INAP PESERTA JKN GUNA MENUNJANG KUALITAS PENGKLAIMAN DI RSUP DR HASAN SADIKIN BANDUNG - Cika Hasanah; Reni Rindiyani Sutisna (Jurnal Teknologi Komputer dan Informatika, 2023)
Based on study in RSUP Dr Hasan Sadikin Bandung found incompleteness of medical resume replenishment of additional diagnosis, doctor's name and signature, additional actions and resumes are not in the file so it can impede the process of claim. The purpose of this research is to know the filling of medical resumes. The method used is quantitative descriptive. Samples were taken from October 2019 – December 2019 many 255 samples using Sugiyono table calculations. The 3-month medical resume population is a total of 9,696 files. Data collection techniques used are observation, interview, literature study, and documentation. The results of research conducted by the author in RSUP Dr Hasan Sadikin Bandung, there were 255 resumes of JKN authors found the highest incompleteness data, Name and Signature of the Doctor as much 125 or 49%. The highest completeness data resume that is in the file and is filled in 223 or 87%. The incomplete filling of medical resumes will affect the quality of the claim, the delay in the claim process can be detrimental to the hospital. The author recommends that a Standard Operating Procedure (SOP) be made for completing the medical resume and giving warning and sanctions to non-compliant Medical Staff Groups.